Pengaruh Keterikatan Pegawai, Komitmen Organisasi, dan Motivasi Kerja Terhadap Kinerja Pegawai PT. PLN (Persero) Palembang - Al Farisi, Salman; Halin, Hamid; Ulum, Bahrul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Factors that influence employee performance are organizational commitment and work motivation. This study aims to determine the effect of Employee Engagement, Organizational Commitment and Work Motivation on Employee Performance at PT. PLN (Persero) UP3 Palembang. This research begins with a survey of 97 employee respondents as a sample at PT. PLN (Persero) UP3 Palembang. The type of data in this study uses primary data obtained directly from respondents using quantitative methods. The data collection technique was carried out by distributing questionnaires to 97 respondents via Googleform. Based on the results of the t-test, the Significant Value of Employee Engagement (X1) is 0.674 > 0.05 and t-count in table 0.421 < t-table 1.661. then, X1 has no effect on Employee Performance (Y). The Significant Value of Employee Commitment (X2) is 0.004 <0.05 and t-count in table 2,964 <t-table 1.661. Then, X2 influences Employee Performance (Y). The significant value of Employee Motivation (X3) is 0.000 <0.05 and t-count in table 4,372 <t-table 1.661. Then, X3 influences Employee Performance (Y). Based on the Coefficient of Determination of Employee Engagement, Organizational Commitment and Work Motivation have a significant influence on Employee Performance of PT PLN (PESERO) UP3 Palembang. And based on the f test, f-count (44,317) > t-table (3,093). There is an influence of Employee Engagement variables (X1), Organizational Commitment (X2) and Work Motivation (X3) on Employee Performance Variables (Y).